Cooperate! A paradigm shift for health equity - Wei-Ching Chang; Fraser, Joy H. (International Journal for Equity in Health, 2017)
The role of competition and cooperation in relation to the goal of health equity is examined in this paper. The authors explain why the win-lose mentality associated with avoidable competition is ethically questionable and less effective than cooperation in achieving positive outcomes, particularly as it relates to health and health equity. Competition, which differentiates winners from losers, often with the winner-takes-all reward system, inevitably leads to a few winners and many losers, resulting in social inequality, which, in turn, engenders and perpetuates health inequity. Competitive market-driven approaches to healthcare–brought about by capitalism, neo-liberalization, and globalization, based primarily on a competitive framework–are shown to have contributed to growing inequities with respect to the social determinants of health, and have undermined equal opportunity to access health care and achieve health equity. It is possible to redistribute income and wealth to reduce social inequality, but globalization poses increasing challenges to policy makers. John Stuart Mill provided a passionate, philosophical defense of cooperatives, followed by Karl Polanyi who offered an insightful critique of both state socialism and especially the self-regulating market, thereby opening up the cooperative way of shaping the future. We cite Hannah Arendt's "the banality of evil" to characterize the tragic concept of "ethical fading" witnessed in business and everyday life all over the world, often committed (without thinking and reflecting) by ordinary people under competitive pressures. To promote equity in health for all, we recommend the adoption of a radically new cooperation paradigm, applied whenever possible, to everything in our daily lives.
Health Studies; Medicine
Keywords: capitalism; competition; competition (psychology); cooperation; cooperative movement; cooperativeness; ethical fading; health & social status; health equity; health services accessibility; health status indicators; interpersonal relations; paradigm shift; paradigms (social sciences)

Orientating disability studies to disablist austerity: applying Fraser’s insights - Dodd, Steven (Disability & Society, 2016)
Many disabled people in Britain have experienced profound challenges brought about by a government policy programme characterised by ‘austerity’. Drawing on the work of Fraser and Polanyi, this article explores new ways in which disability studies can become theoretically orientated to the task of explaining and challenging what has become an issue of overbearing importance for many disabled people. It is argued that Fraser’s notion of bivalency encapsulates the combination of cultural and economic challenges which characterise ‘disablist austerity’. Fraser’s development of Polanyi’s work is used to argue that disability studies should be orientated to large-scale economic challenges as well as cultural and discursive concerns that are more often the object of study in the field.
Health Studies; Disability Studies
Keywords: Great Britain; austerity; budget; conceptual structures (information theory); culture; disability studies; disablism; government policy; marketisation; people with disabilities - psychology; practical politics; public welfare; recognition; redistribution; research methodology; social justice; socioeconomic factors; triple movement